Battleground Masculinity: Gendertroublers and Gatekeepers in Oliver Stone's Platoon (1986) - Christina Judith Hein (Current Objectives of Postgraduate American Studies)
In the years following its release in 1986, Oliver Stone's Vietnam war film, Platoon“, received a great amount of attention in academia. A critical look from the vantage point of contemporary Queer and Gender Studies, however, can still contribute valuably and reveal issues hitherto untouched. My paper discusses how, besides fighting a military war, the film's three protagonists are deeply involved in negotiating masculinity as they assume positions not only in an oedipal arrangement but also in the contest between gendertroublers and borderpatrols.